Analisis Model Peningkatan Keputusan Pembelian Kartu Provider Melalui Tingkat Kunjungan Website (Studi pada Pengguna Kartu Provider SIMPATI di Untirta) - Lutfi Lutfi; Ryno Akanoval (Magister Manajemen - Universitas Sultan Ageng Tirtaysa, 2022)
This study aims to determine the effect of oniline promotion (X1) and price discount (X2) on purchasing decisions (Y) mediated by the level of website visits (Y) on Telkomsel card provider users. The method used in this research is quantitative research with associative approach. The population in this study were all students majoring in Management at Sultan Ageng Tirtayasa University. The sample of this study was students majoring in Management at Sultan Ageng Tirtayasa University who used the Telkomsel provider card using the snowball sampling method. The data analysis technique used in this study is Structural Equation Modeling (SEM) by using the SmartPLS 3.3 software of the student version. The results showed that: (1) oniline promotion has a positive and insignificant effect on purchasing decisions. (2) oniline promotion has a positive and significant effect on the level of website visits. (3) price discounts has a negative and insignificant effect on purchasing decisions. (4) price discount has a positive and significant effect on the level of website visits. (5) the level of website visits has a positive and significant effect on purchasing decisions. (6) the level of website visits mediate the effect of oniline promotion on purchasing decisions. (7) the level of website visits mediate the effect of price discount on purchasing decisions